Um estudo sobre a formação contínua do professor na perspectiva crítico-política - Haydn, Érika de Oliveira (2018)
This study aims to analyze the relationship between formative proposals inside the school environment and their socio-historical-cultural context, in order to develop a proposal for a critical-collaborative formation stemming from the experiences lived by the participants of this research. The study is based in the Socio-Historical-Cultural Activity Theory, which understands that the activities of life are spaces for the development of human relations. In this perspective, the development of the participants of a given context is produced in a dialectical process, though critical reflection and through the actions of the subjects while they transform their own reality. This research focused on the training space for teachers in the “Jornada Especial Integral de Formação” (Special Integral Training Workshop), and the participants were a group of twelve teachers, a pedagogical coordinator, a school principal, a teaching supervisor and this researcher, who is also a Physical Education teacher in a municipal school located in the southern region of São Paulo. The study was conducted under the light of the Critical Collaborative Research, as an intervention-investigation assisted by the theoretical framework of the Socio-Historical-Cultural Activity Theory. We analyzed: 1) the Political Pedagogical Project of the school, 2) audio-recorded semi-structured interviews carried out with six subjects and 3) the training space. The analyses were performed based on the four-action cycle proposed by Smyth (1992): describe, inform, confront and reconstruct. The results of the investigation allowed us to perceive the distance between the socio-historical-cultural context and the pedagogical practice of the school. With this, a critical-collaborative training plan was proposed, to be shared with the school and submitted to the supervisors of the regional Board of Education